Islamic Populism Politics and Its Threat to Indonesian Democracy - Zainuddin Syarif; Abd Hannan (IAIN Ponorogo, 2020)
Abstract: The study focuses on discussing the phenomena of Islamic populism politics, its role and impact to the future Indonesian democracy. More specifically this study addressed two major issues, namely Islamic populism, and democracy in Indonesia. By using qualitative study and analysis through critical sociology theory, this study found that the phenomena of Islamic populism as a global political phenomenon which occurred in numerous countries in the world affected the process of democracy in Indonesia. This is shown by the occurrance of primordialism issue, mainly roots from the Islamic identity. In fact, the problem of Islamic populism politics for the construction of Indonesian democracy system could be seen from two factors; First, Islamic populism politics which practically uses the religion issue has triggered religious intolerance. This gives impacts on the uprise of exclusivism which ends up in sentimental behavior; Second, exploitation of Islamic populism issue gives negative consequences on the incline of intolerance behavior trend in politic sector both politics in the legislative area, especially the political dynamics and at the executive level.الملخص: تركز الدراسة على مناقشة ظواهر السياسة الشعوبية الإسلامية ودورها وتأثيرها على الديمقراطية الإندونيسية المستقبلية. هناك ثلاث بيانات للمشاكل في الدراسة ؛ الشعبوية الإسلامية والديمقراطية في إندونيسيا. باستخدام الدراسة والتحليل النوعيين من خلال نظرية علم الاجتماع النقدي ، وجدت هذه الدراسة أن ظاهرة الشعبوية الإسلامية السياسة العالمية التي حدثت في العديد من البلدان في العالم أثرت على عملية الديمقراطية في إندونيسيا. ويتجلى ذلك من خلال وقوع قضية البدائية التي تعود جذورها بشكل أساسي إلى الهوية الإسلامية. في الواقع ، يمكن رؤية مشكلة استخدام السياسة الشعوبية الإسلامية لبناء نظام ديمقراطي إندونيسي من عاملين ؛ أولاً ، تسببت السياسة الشعوبية الإسلامية التي تستخدم مسألة الدين عملياً في عدم التسامح في القطاع الديني. ويؤثر هذا على صعود النزعة الاستئثارية التي تنتهي بالسلوك العاطفي ؛ ثانيًا ، يؤدي استغلال قضية الشعبوية الإسلامية إلى عواقب وخيمة على ميل نزعة سلوك التعصب في القطاع السياسي.Abstrak: Studi ini fokus membahas fenomena politik populisme Islam, peran dan pengaruhnya terhadap masa depan demokrasi di Indonesia. Terdapat dua permasalahan penelitian yang diangkat dalam kajian ini; fenomena populisme Islam, dan terakhir adalah demokrasi di Indonesia. Dengan menggunakan jenis penelitian kualitatif dan analisa melalui teori sosiologi kritis, studi ini mendapati temuan bahwa fenomena populuisme Islam yang terjadi di banyak negara dunia, saat ini juga telah mewarnai demokratisasi di Indonesia. Demikian ditandai oleh mengemukanya penggunaan isu primordialisme, terutama yang mengakar pada aspek identitas. Dalam kenyataannya, problem penggunaan politik populisme Islam terhadap bangunan sistem demokrasi di Indonesia dapat dilihat dari dua hal; Pertama, politik populisme Islam yang dalam praktiknya memanfaatkan isu agama telah menimbulkan intoleransi di sektor keagamaan. Hal ini berdampak negatif terhadap bangkitnya eksklusivisme yang berujung pada perilaku anarkisme dan kekerasan yang mengatasnmakan agama; Kedua, eksploitasi isu populisme Islam berakibat buruk terhadap realitas politik. Baik politik di wilayah legislatif, terlebih lagi dinamika politik di level eksekutif.